Video Verslag. (Rotterdam : Rotterdamse Kunststichting, 1973)
Gijzen, Wim ; van Munster, Jan ; Man ray ; Engels, Pieter ; Segal, George ; Oppenheim, Dennis ; Schippers, K. ; Gribling, Frank ; Jaffe, Lee ; Tas, Henk ; Enk, Frits ; Fox, Terry ; Melchert, Jim ; etc.
Video, Lijnbaancentrum, Rotterdamse Kunststichting, Rotterdam, 9 februari - 12 maart 1973
boek